Paecilomyces lilacinus and Verticillium chlamydosporium Fungi as Biological Control of Fasciolosis - Ahmad, Riza Zainuddin (Indonesian Bulletin of Animal and Veterinary Sciences, 2013)
Fasciolosis is a worm disease caused of Fasciola gigantica and an important problem in husbandry especially for cattle. Controlling of this worm disease can be conducted by prevention and treatment. The use of antihelminthic is commonly causes a resistance problem. Natural control by mold such as Paecilomyces lilacinus and Verticillium chlamydosporium can be applied to reduce egg of F. gigantica. Although it was recently found, in vitro study gave satisfied result. This gives a new hope in controlling the disease although the extend application still needs to be studied. This paper discussed about the use of P. lilacinus and V. chlamydosporium for reducing F. gigantica population. Â  Key words: Natural control, F. gigantica, P. lilacinus, V. chlamydosporium